Complex structure of the carbon arc discharge for synthesis of nanotubes. (6th June 2017) - Vekselman, V; Feurer, M; Huang, T; Stratton, B; Raitses, Y
Abstract: Comprehensive non-invasive spectroscopic techniques and electrical measurements of the carbon arc revealed two distinguishable plasma synthesis regions in the radial direction normal to the arc axis. These regions, which are defined as the arc core and the arc periphery, are shown to have very different compositions of carbon species with different densities and temperatures. The colder arc periphery is dominated by carbon diatomic molecules (C2 ), which are in the minority in the composition of the hot arc core. These differences are due to a highly non-uniform distribution of the arc current, which is mainly conducted through the arc core populated with carbon atoms and ions. Therefore, the ablation of the graphite anode is governed by the arc core, while the formation of carbon molecules occurs in the colder arc periphery. This result is consistent with previous predictions that the plasma environment in the arc periphery is suitable for synthesis of carbon nanotubes.